Dysregulated gliotoxin biosynthesis attenuates the production of unrelated biosynthetic gene cluster-encoded metabolites in Aspergillus fumigatus. Issue 4 (April 2018) - Doyle, Sean; Jones, Gary W.; Dolan, Stephen K.
Abstract: Gliotoxin is an epipolythiodioxopiperazine (ETP) class toxin, contains a disulfide bridge that mediates its toxic effects via redox cycling and is produced by the opportunistic fungal pathogen Aspergillus fumigatus . The gliotoxin bis -thiomethyltransferase, GtmA, attenuates gliotoxin biosynthesis in A. fumigatus by conversion of dithiol gliotoxin to bis -thiomethylgliotoxin (BmGT). Here we show that disruption of dithiol gliotoxin bis -thiomethylation functionality in A. fumigatus results in significant remodelling of the A. fumigatu s secondary metabolome upon extended culture. RP-HPLC and LC–MS/MS analysis revealed the reduced production of a plethora of unrelated biosynthetic gene cluster-encoded metabolites, including pseurotin A, fumagillin, fumitremorgin C and tryprostatin B, occurs in A. fumigatus Δ gtmA upon extended incubation. Parallel quantitative proteomic analysis of A. fumigatus wild-type and Δ gtmA during extended culture revealed cognate abundance alteration of proteins encoded by relevant biosynthetic gene clusters, allied to multiple alterations in hypoxia-related proteins. The data presented herein reveal a previously concealed functionality of GtmA in facilitating the biosynthesis of other BGC-encoded metabolites produced by A. fumigatus .